Pengaruh Edukasi Pasar Modal Terhadap Minat Investasi Saham Melalui Persepsi Risiko: Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Lampung - Ananda Putri Kusuma; Tina Miniawati Barusman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of capital market education on students’ stock investment interest, with risk perception as a mediating variable. The research was conducted among students of the Faculty of Economics and Business, University of Lampung, who had participated in capital market education programs. This study employed a quantitative explanatory research approach. Data were collected through Likert-scale questionnaires (1–5) from 363 respondents and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that capital market education has a significant effect on both risk perception and stock investment interest. Risk perception demonstrates the strongest influence on students’ investment interest. Furthermore, risk perception plays a significant mediating role in the relationship between capital market education and stock investment interest. These findings suggest that capital market education becomes more effective in enhancing investment interest when it successfully shapes positive, rational, and well-managed risk perceptions. This study contributes theoretically to the development of behavioral finance and human capital perspectives and provides practical implications for universities and capital market authorities in designing educational programs that not only enhance financial knowledge but also foster healthy risk perceptions among young investors.